2011
DOI: 10.1111/j.1742-4658.2011.08394.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of subunit assembly and function of the Saccharomyces cerevisiae RNase H2 complex

Abstract: RNase H2 of Saccharomyces cerevisiae consists of three essential subunits (Rnh201, Rnh202 and Rnh203) and plays a critical role in the removal of RNA incorporated in duplex DNA. In the present study, we purified individual subunits and heterodimeric subcomplexes to examine the assembly and biochemical function of subunits of RNase H2 in vitro. Reconstitution experiments revealed that Rnh202 and Rnh203 first form a subcomplex, followed by the recruitment of Rnh201 to complete complex formation. Rnh201 alone or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The eukaryotic homologue is the RNASEH2A subunit, and although it has no enzyme activity by itself, it forms an active heterotrimeric complex together with the accessory RNASEH2B and RNASEH2C subunits [12,14,24,25]. A high level of structural similarity between prokaryotic RNase HII and eukaryotic RNASEH2A was first shown when the crystal structure of the mouse enzyme was solved by Hollis and colleagues [26].…”
Section: Structural Studies Of Rnase H2 Enzymesmentioning
confidence: 96%
See 1 more Smart Citation
“…The eukaryotic homologue is the RNASEH2A subunit, and although it has no enzyme activity by itself, it forms an active heterotrimeric complex together with the accessory RNASEH2B and RNASEH2C subunits [12,14,24,25]. A high level of structural similarity between prokaryotic RNase HII and eukaryotic RNASEH2A was first shown when the crystal structure of the mouse enzyme was solved by Hollis and colleagues [26].…”
Section: Structural Studies Of Rnase H2 Enzymesmentioning
confidence: 96%
“…For example, a PIP-box [PCNA (proliferating-cell nuclear antigen)-interacting protein box] motif at the C-terminus of the RNASEH2B subunit guides the interaction between RNase H2 and PCNA [12] and its localization to replication foci [28]. Experiments with the S. cerevisiae proteins suggest that the B subunit may also have a role in substrate binding [25].…”
Section: Structural Studies Of Rnase H2 Enzymesmentioning
confidence: 97%
“…To confirm that inactivation of RNase H1 and H2 allows for direct transcript RNA repair of a DSB in homologous DNA, we conducted a complementation test in the cis system using a vector expressing either a catalytically inactive mutant of RNH201, rnh201 -D39A 15 , or wild-type RNH201 . Results showed that when wild-type RNH201 was expressed from the plasmid in rnh1 rnh201 spt3 cells, there were no His + colonies following DSB induction ( Extended Data Fig.…”
mentioning
confidence: 99%
“…Rnh201 is the catalytic subunit of the RNase H2 complex, which protects genome integrity by removing RNA nucleotides incorporated into DNA during replication and/or Okazaki fragment synthesis (Nguyen et al 2011;Wahba et al 2011;Amon and Koshland 2016). Rnh201 plays a key role in DNA damage response and DNA replication processes (Allen-Soltero et al 2014).…”
Section: Rnh201mentioning
confidence: 99%